Biobased copolyesters: synthesis, crystallization behavior, thermal and mechanical properties of poly(ethylene glycol sebacate-co-ethylene glycol 2, 5-furan dicarboxylate). Issue 23 (1st March 2017) - Wang, Guoqiang; Jiang, Min; Zhang, Qiang; Wang, Rui; Zhou, Guangyuan
Abstract : A series of biobased copolyesters, poly(ethylene sebacate- co -ethylene 2, 5-furandicarboxylate) (PESF), were synthesized from available biobased ethylene glycol (EG), sebacic acid (SA) and 2, 5-furandicarboxylic acid (FDCA). Abstract : A series of biobased copolyesters, poly(ethylene sebacate- co -ethylene 2, 5-furandicarboxylate) (PESF), were synthesized from available biobased ethylene glycol (EG), sebacic acid (SA) and 2, 5-furandicarboxylic acid (FDCA) through a two-step melt polycondensation method. The composition, molecular weight and its distribution, crystal structure, and crystallization behavior of PESFs were investigated by 1 H NMR, GPC, WAXD, and DSC methods, respectively. Tensile properties were also evaluated. While increasing the content of the FDCA unit, the glass transition temperatures of PESFs increased and the crystallization rates of PESFs decreased. Compared with poly(ethylene sebacate) (PES), PESF20 showed two melting peaks due to the formation of secondary crystals (small and imperfects crystals) caused by the incorporation of FDCA during the isothermal crystallization process. POM data showed that the nucleation density of PESF10 and PESF20 increased and the size of spherulites decreased due to the chain irregularity caused by randomization distribution with the introduction of FDCA. However, the crystal structure remained unchanged. Ring-banded spherulites were not detected for PESF20 in a wide temperature range (28–44 °C) as the incorporation of FDCA can restrict lamellar twisting and scrolling of PES segments. The thermal transition and mechanical properties of copolymers are tunable with the composition.